Netherlands Yearbook of International Law Volume 41, 2010
XIV, 546 p.
Keywords: The Netherlands Yearbook of International (NYIL) Law has two main aims. It offers a forum for the publication of scholarly articles of a more general nature in the area of public international law, including the law of the European Union. In addition, each Yearbook provides an overview of the state practice of the Netherlands, including Dutch judicial decisions involving questions of public international law. In this volume of NYIL ‘necessity’ is the focus of analysis. Necessity plays a significant role in any legal system, as unpredictable or extraordinary situations can require the adoption of measures departing from the normally applicable law in order to protect basic values and fundamental interests. International law is not an exception. The scholarly articles in this volume discuss the role of the principle of necessity in different fields of international law, namely in conflict and security law, humanitarian law, human rights law, environmental law, international trade law, and foreign investment law. Each contribution reflects on central questions of the theme of necessity, such as the nature of the necessity plea, the role of the Articles on State Responsibility and general customary law, and the use of cross-references in case law to international decisions in other, but in terms of necessity related, fields of international law.